Modelling and simulation of flexible aircraft : handling qualities with active load control - Andrews, Stuart P. (Cranfield University, 2011)
The study of the motion of manoeuvring aircraft has traditionally considered the aircraft to be rigid. This simplifying assumption has been shown to give quite accurate results for the flight dynamics of many aircraft types. As modern transport aircraft have developed however, there has been a marked increase in the size and weight of these aircraft. This trend is likely to continue with the development of future blended-wing-body and supersonic transport aircraft. This increase in size and weight has brought about a unique set of aeroelastic and handling quality issues. The aerodynamic forces and moments acting on an aeroplane have traditionally been represented using the aerodynamic derivative approach. It has been shown that this quasisteady aerodynamic model inadequately predicts the aircraft’s stability characteristics, and that the inclusion of unsteady aerodynamics “greatly improves the fidelity” of aircraft models. This thesis thus presents a novel numerical simulation of an aeroelastic aeroplane for real-time analysis. The model is built around the standard six degree-of-freedom equations of motion for a rigid aeroplane using the mean-axes system, and includes unsteady aerodynamics and structural dynamics. This is suitable for pilot-in-the-loop simulation, handling qualities and flight loads analysis, and control law development. The dynamics of the structure are modelled as a set of normal modes, and the equations of motion are realised in state-space form. The unsteady aerodynamic forces acting on the aeroplane are described by an indicial state-space model, including unsteady tailplane downwash and compressibility effects. An implementation of the model is presented in the MATLAB/ Simulink environment. The interaction between the flight control system, the aeroelastic system and the rigidbody motion of the aeroplane can result in degraded handling qualities, excessive actuator control, and fatigue problems. The introduction of load alleviation systems for the management of loads due to manoeuvres and gusts is also likely to result in the handling qualities of the aeroplane being degraded. This thesis presents a number of studies into the impact of structural dynamics, unsteady aerodynamics, and load alleviation on the handling qualities of a flexible civil transport aeroplane. The handling qualities of the aeroplane are assessed against a number of different handling qualities criteria and flying specifications, including the Neal-Smith, Bandwidth, and CAP criterion. It is shown that aeroelastic effects alter the longitudinal and lateral-directional characteristics of the aeroplane, resulting in degraded handling qualities. Manoeuvre and gust load alleviation are similarly found to degrade handling qualities, while active mode control is shown to offer the possibility of improved handling qualities.
Keywords: Flexible; Elastic; Civil Transport; Aeroplane; Flight Dynamics; Handling Qualities; Aeroelasticity; Aeroservoelasticity; Structural Dynamics; Unsteady Aerodynamics; Load Alleviation